(untitled) (Revista do Tribunal Regional Federal da 3ª Região, 2013)
It is argued that, although the benign retroactivity of foreign exchange rules that complement blank criminal types is not admissible as a rule, the use of international credit cards to purchase goods for commercial purposes has never been criminally typical - it only constitutes an administrative infraction.